Relationship between environment and spatio-temporal evolution of small pelagic fish in the canary upwelling system (NW Africa) - (:unkn) unknown (My University, 2016)
The North West African upwelling system off Morocco, Mauritania, Gambia and Senegal is the most productive system in the world in terms of primary productivity. This productivity results in a large fish biomass dominated by small pelagic fish which are the main living resources exploited in the region. In a context of shared management of fisheries resources by several countries in the region, understanding the factors that control the spatial distribution of populations of small pelagic fish and the evolution of their abundances is a crucial issue for fisheries and the socio-economic development of the region. The main objective of this thesis is to describe the seasonal and interannual variations of the marine environment of the Canary upwelling along the Northwest coast of Africa and to link these variations with the spatio-temporal dynamics of the main small pelagic species of commercial importance of this zone. We have used different sets of data available and developed different approaches in order to have a complete view of the functioning of this ecosystem. Thus, we have combined satellite data, acoustic scientific survey data, fishing statistics and analysis of otolith shapes. Along th NW African coasts ( 10° - 35° N), our data allowed us to identify three regions with a well-differentiated seasonality and intensity of upwelling. The region has a high latitudinal and temporal variability of environmental conditions. The southern part of the zone (between 10° and 24° N) is characterized by warmer and richer Chlorophyll-a waters than the northern part. The majority of the variability of the environmental parameters studied is due to seasonality (> 60%). During the study period (2002-2012), we noted a significant warming trend ranging from 0.01° C to 0.04°C. yr-¹ and a general reinforcement of ipwelling, but a downward trend in Chl a concentration in the whole study area. There is a south-north latitudinal gradient of the phenology
Keywords: African Research